Simulation Test System for Development and Testing of Electrical Drive Systems - Franchi, Norman; Wellmann, Sebastian (Vieweg+Teubner Verlag | Springer Fachmedien Wiesbaden GmbH, 2011)
The proposed approach focuses on the realization of a modular test stand concept for electrical drives that combines automated, high-quality and precise Hardware-in-the-Loop simulation testing with the development of the corresponding embedded control software. The real system under test consists of an electronic control unit, the corresponding electrical engine and a controllable dynamometer for dynamic load emulation.
elib2cris::1512001600,franchi2011
Keywords: Electrical Drives; Engine Test Stand; Hardware-in-the-Loop; Control Prototyping; Dynamic Load Emulation; Modular Design; Combined Development and Test Environment